Experimentally quantified and computational anisotropic damage rules for flax fabric composites. (January 2018) - Panamoottil, SM; Das, R; Jayaraman, K
Continuum damage mechanics models have been used for predicting failure in composites for several years now. However, their application to natural fibre composites is quite recent. In this work, an approach for evaluating damage processes in natural fibre composite has been developed by combining experimentally quantified damage rules with discrete representations of fabric geometry. This approach is demonstrated by predicting the tensile failure of both thermoplastic-based and thermoset-based flax fabric composites. Numerical models have been developed to estimate the damage rules from the fibre, matrix and interface properties incorporated into representative volume element (RVE) models of the composites. While both the experimentally quantified and numerically obtained sets of damage rules yield satisfactory predictions, the use of these numerical rules leads to predictions that are close to, and in some cases, better than those obtained from the quantified rules.